Effectiveness of take ACTION online naloxone training for law enforcement officers - Chin Hwa Dahlem; Rohan Patil; Lara Khadr; Robert J. Ploutz-Snyder; Carol J. Boyd; Clayton J. Shuman (BMC, 2023)
Abstract Background Training law enforcement officers (LEOs) to administer naloxone is a recommended strategy to reduce overdose deaths in the United States. To achieve this, an evidence-based and scalable naloxone training curriculum that is easy to use and readily scalable is needed. Convenient web-based training is a flexible method for delivering educational interventions particularly for LEOs who have irregular or shifting schedules. This study examined the effectiveness of a comprehensive web-based naloxone training that was created in partnership with LEOs on their knowledge, confidence, and attitudes regarding naloxone. Methods From May 2019 to September 2020, five law enforcement departments from Michigan participated in web-based naloxone training. A total of 182 LEOs (77% male) were in the final sample based on matching pre-and post-test surveys. LEOs were assessed on knowledge, confidence, and attitudes towards naloxone. Negative binomial and Poisson regression was conducted to assess associations between knowledge, confidence, and attitudes towards naloxone before and after training. Results Significant improvements in overdose knowledge and confidence were revealed across all departments with median (IQR) total composite scores for knowledge increasing from 35 (32, 37) to 40 (39, 42) (p < 0.01) and confidence increasing from 18.5 (15, 20) to 20 (20, 25) (p < 0.01). Median (IQR) attitude scores did not change. Conclusion Our web-based naloxone training was effective in improving knowledge and confidence for LEOs but did not significantly improve LEOs attitudes towards naloxone across most departments. The web-based format is readily scalable and quickly disseminated and meets the immediate need for LEO overdose training. Additional intervention is needed to address the negative attitudes of LEOs regarding naloxone.